Posisi Ushul Fikih dalam Metodologi Ekonomi Islam - Wahid, Wawan Gunawan Abdul (IAIN Salatiga, 2014)
Islamic Economics is an entity of thought and practice that currently writhingin Muslim communities. Each entity has certain ideas of its own methodology.So it is with Islamic economics. Since the product of intentional since thebeginning of Islamic economics is different from the conventional economywas certainly one of the distinguishing framework called ushul fiqh. Thispaper presents the position of ushul fiqh methodology of Islamic economics.To confirm the significance of the position shown several such productswhere the Islamic economic jurisprudence fiqh perspective when used as awhole shows a different product than the product of conventional economics.